PENGARUH MODEL PEMBELAJARAN PROBLEM POSING TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VI SD/MI - Arifah, Fifan -; Mangkuwibawa, Hilman; Mahmud, Muhammad Rifqi (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2025)
The problem that occurs in class VI students at MI Miftahul Huda Bandung is the low results of students' mathematics learning. The test results show that the average grades for classes 6A, B, C respectively are 42.5; 34.8; and 39.9. This research aims to determine the effect of the problem posing learning model on the mathematics learning outcomes of class VI students at MI Miftahul Huda Bandung. This research was conducted using a quasi-experimental method, pretest-posttest non-equivalent control group design. The population in this study were all class VI students at MI Miftahul Huda Bandung, totaling three classes with classes A and B as samples having the same group. Data processing was carried out using a normality test and paired t-test on the pretest and posttest scores for the experimental class. The normality test results show a figure of 0.200 in the pretest and posttest value data. The results of the paired t-test for the experimental class produced a significance value smaller than 0.001 so that it was concluded that the problem posing learning model had an effect on the mathematics learning outcomes of class VI students at MI Miftahul Huda Bandung.